Produktivitas Nelayan, Kapal dan Alat Tangkap di Wilayah Pengelolaan Perikanan Indonesia - Yonvitner Yonvitner (Universitas Gadjah Mada, 2007)
Fisheries productivity is defined as a comparison of production to fishing effort.The Fishing effort can be the number of fishers, fishing boats or fishing gears. This paper was developed from analysis of Indonesia Fisheries Statistic data in the period of 1990-2001 at 9 regions of fishery management in Indonesia. It was assumed that the catch by fisherman in each region will be landed at the same region. The results showed that productivity level of fisherman was lowest at WPP-9 (Indian Ocean) with a value 1,2 ton per year (an average 100 kg per month per fisher). The highest productivity of fisherman reached 3.1 ton in 1999 at WPP-5 (Sulawesi Sea and Tomini Gulf). The productivity of fishing boat was ranged from 7.8 ton to 16.4 ton per year per fishing boat. Then the productivity of gear was from 5,0 ton per gear per year to 13,5 ton per gear per year. From this result, it can be predicted that the distribution of fishing gear, fishing boat and fisherman in 9-WPP was not equally proportional. For sustainability life of the fisheries, it need a policy which may increase to economic benefit of fisherman and fishing activity.